Five Finger Hypnosis for Post-Flood Psychological Disorders - Silvitasari, Ika; Listyorini, Dewi; Wahyuni (P3M Universitas 'Aisyiyah Surakarta, 2024)
Background: Central Java is a province that often experiences floods and Surakarta is the city with the second highest flooding after Semarang. Floods that occur will cause several impacts, one of which is psychological impacts. Psychological impacts in the form of anxiety, stress and clinical depression and mental health problems will interfere with daily activities. Objective: to determine the Effect of Five Finger Hypnosis on Psychological Symptoms of Post-Flood Society. Methods: this study was conducted in the Sangkrah area with 45 respondents according to inclusion and exclusion criteria. The research instrument used was DASS-21 and analyzed using the Wilcoxon test. Results: the significance value of psychological stress disorders (P-Value) = 0.000 <0.05; the significance value of psychological anxiety disorders (P-Value) = 0.001 <0.05; and the significance value of psychological anxiety disorders (P-Value) = 0.003 <0.05. There is an effect of five-finger hypnosis therapy on post-flood psychological disorders in the Sangkrah area, Surakarta before and after being given five-finger hypnosis therapy. Conclusion: five finger hypnosis therapy can be used to reduce psychological disorders